Unveiling Corruption in Kola Eke’s Poetry: A New Historicist Approach - Ilechukwu, Ijeoma Susan (NIU Journal of Humanities, 2024)
This paper critically examines Kola Eke’s poetic exploration of corruption within Nigeria’s historical scene. Positioned as a Third-Generation Nigerian poet, Eke follows in the tradition of prominent Second Generation poets like Niyi Osundare, Tanure Ojaide, Odia Ofeimun etc. who have used their poetic works to highlight the socio-political and economic challenges that have plagued Nigeria since its independence in 1960. The study emphasises Eke’s significant contributions to the discourse on corruption, particularly within Nigeria’s civil service, electoral commission, and broader political leaderships. By employing a New Historicist approach, the paper analyses Eke’s imaginative representation of corruption to uncover its various forms and historical roots, while also considering the poet’s suggestions for mitigating these issues. The findings reveal that Eke’s work powerfully critiques the pervasive corruption in Nigeria, shedding light on its destructive and debilitating impacts on the nation. Keywords:   Corruption, New Historicism, Political, Democracy, Contemporary, Civil Service